Penggunaan Madu dalam Sediaan Topikal sebagai Pelembap Kulit - Ni Kadek Lidia Ayu Aristina; I Gede Made Suradnyana; Ni Made Sukma Sanjiwani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Skin is the body's outermost organ, enveloping all parts of the human body. When the water content in the stratum corneum (SC) drops below 10%, the skin can become scaly, rough, and dry. Honey possesses humectant, emollient, and antioxidant properties, making it an effective moisturizer. The humectant properties of honey stem from its high sugar content, particularly glucose and fructose. These sugars form hydrogen bonds with water, helping to retain moisture in the skin and thus providing a hydrating effect. Additionally, honey contains vitamin C, alpha hydroxy acids, and flavonoids, which contribute to the elasticity and firmness of the skin. Therefore, it is important to conduct a narrative review on the use of honey as a moisturizer in topical preparations, which can serve as a reference for future research. The literature search for this review was conducted using databases such as Google Scholar, Garuda Journal, MDPI, ResearchGate, and Publish or Perish, employing specific inclusion and exclusion criteria. The findings concluded that honey can be used as a moisturizer in various dosage forms, including body scrubs, anti-aging and moisturizing creams, serums, peel-off gel masks, lip moisturizers, and lip scrubs. The concentration of honey used in these formulations depends on the dosage form, its intended function in the formula (whether as an active substance, humectant, or emollient), and the comparison of honey concentration with other ingredients.